Hydrothermal synthesis of Co3O4 nanosheets and its application in photoelectrochemical water splitting. Issue 10 (3rd October 2017) - Bazrafshan, Hamed; Shajareh Touba, Razieh; Alipour Tesieh, Zahra; Dabirnia, Saeideh; Nasernejad, Bahram
ABSTRACT: In this study, Co3 O4 nanosheets were synthesized through hydrothermal method using cobalt nitrate hexahydrate. X-ray diffraction, diffuse reflectance spectra, Fourier transform infrared spectroscopy, energy-dispersive X-ray spectroscopy, and field emission scanning electron microscopy were applied to investigate the properties of as-synthesized samples. Ultimately, the electrochemical and photoelectrochemical properties were evaluated by Mott–Schottky analysis and measuring photoconversion efficiency of Co3 O4 nanosheets. The results indicated that Co3 O4 nanosheets exhibited a maximum efficiency of 0.92% for water electrolysis under simulated 1.5 global sunlight air mass, which further suggests the excellent potential of Co3 O4 nanosheets for application in hydrogen generation through photocatalytic water splitting.